An image cryptography method by highly error-prone DNA storage channel - Zan, Xiangzhen; Chu, Ling; Xie, Ranze; Su, Yanqing; Yao, Xiangyu; Xu, Peng; Liu, Wenbin (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Rapid development in synthetic technologies has boosted DNA as a potential medium for large-scale data storage. Meanwhile, how to implement data security in the DNA storage system is still an unsolved problem. Methods: In this article, we propose an image encryption method based on the modulation-based storage architecture. The key idea is to take advantage of the unpredictable modulation signals to encrypt images in highly error-prone DNA storage channels. Results and Discussion: Numerical results have demonstrated that our image encryption method is feasible and effective with excellent security against various attacks (statistical, differential, noise, and data loss). When compared with other methods such as the hybridization reactions of DNA molecules, the proposed method is more reliable and feasible for large-scale applications.